Voltammetric determination of isoprenaline in pharmaceutical preparations using a copper(II) hexacyanoferrate(III) modified carbon paste electrode - Bonifacio, V. G.; Marcolino, L. H.; Teixeira, MFS; Fatibello-Filho, O. (Elsevier B.V., 2004)
The electroanalytical determination of isoprenaline in pharmaceutical preparations of a homemade carbon paste electrode modified with copper(II) hexacyanoferrate(III) (CuHCF) was studied by cyclic voltammetry. Several parameters were studied for the optimization of the sensor such as electrode composition, electrolytic solution, pH effect, potential scan rate and interferences in potential. The optimum conditions were found in an electrode composition (in mass) of 15% CuHCF, 60% graphite and 25% mineral oil in 0.5 mol l(-1) acetate buffer solution at pH 6.0. The analytical curve for isoprenaline was linear in the concentration range from 1.96 x 10(-4) to 1.07 x 10(-3) mol l(-1) with a detection limit of 8.0 x 10(-5) mol l(-1). The relative standard deviation was 1.2% for 1.96 x 10(-4) mol l(-1) isoprenaline solution (n=5). The procedure was successfully applied to the determination of isoprenaline in pharmaceutical preparations; the CuHCF modified carbon paste electrode gave comparable results to those results obtained using a UV spectrophotometric method. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: modified carbon paste electrode; copper(II) hexacyanoferrate(III); voltammetric determination; isoprenaline; pharmaceutical preparations